Program Tahsin Surat Al-Fatihah Bagi Santri TPQ Ar-Rahmah Nggotean Desa Pacet - Muhammad Ryan Kurniawan; Muhammad Cepi Saipulloh; Muhammad Irfandi Cahyo; Abdul basid (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Partners in community service activities are TPQ Ar Rahmah Nggotean Pacet Village. Based on the results of the analysis of the situation above, there are problems that need to be resolved regarding with the lack of quality reading students due to the following things; 1) TPQ educators are still not optimal in classroom management because they are often late and do not come. 2) The quality of some educators is still lacking, especially in terms of teaching and makhraj. 3) The quality of teaching materials that are too difficult for students and seem pushy. From the problems identified above, discussions were held with the TPQ Coordinator Ar Rahmah Nggotean of Pacet Village, namely Mrs. Aina, the problem that was agreed to be resolved was through the Tahsin Surat Al-Fatihah program for students, it was hoped that students could read Al-Fatihah with good and true, which at least in the reading of the letter Al-Fatihah santri there is no Lahn Jaly or fatal letter pronunciation errors. The teaching method used by the executor is Classical Reading Listening Pure, with the educator exemplifying the reading of the letter Al-Fatihah verse by verse then imitated by the students and then repeated up to 2 to 3 times, then the Classical Individual, namely by one by one the students read the letter Al-Fatihah and immediately corrected by the teacher. Based on the results of this community service activity, it can be concluded that there is an increase in the quality of reading Surah Al-Fatihah for students of TPQ Ar Rahmah Nggotean, especially from the long, short and makhraj side after the Surah Al-Fatihah Tahsin Program activities, so that it can help TPQ a little to improve the quality of reading of the students TPQ Ar Rahmah Nggotean.